Pelatihan Membuat Media Pembelajaran Dengan Aplikasi Ulead Video Studio 11 Bagi Guru SMP dan Mahasiswa - Agus Susilo; Ratna Wulansari (Jurnal Pengabdian Masyarakat Madani, 2021)
In this era of globalization, teachers and students must be accustomed to using or utilizing online and offline applications to support learning activities. In the implementation of this community service activity, the activity implementation team uses direct or face-to-face methods. So the activity participants directly listened to the presentation and practice for designing media with the Ulead Video Studio 11 application. This community service activity was carried out in a shophouse on Jalan Simpang Priuk, Lubuklinggau City for 2 days. The result of this community service activity is that during the activity, teachers and students who take part in the activity are guided by presenters who already have experience in using the Ulead Video Studio 11 application. In addition, participants have also brought their own equipment, in the form of laptops and data packages to find materials that will be used in training activities. The implementation of community service activities carried out for 2 days, including installing applications, introducing the use of Ulead Video Studio 11, and converting them into MP4 learning media. This activity ended with a photo with the presenters and participants in community service activities. The conclusion is that the training to make learning media using the Ulead Video Studio 11 application for junior high school teachers and students in Lubuklinggau City is very beneficial and provides experience for the participants of the activity. The participants who are teachers and students can apply it in activities related to learning. Besides being simple, the use of the Ulead Video Studio 11 application can be used offline without an internet network.